Evidentiality in J-blogs articles written in Spanish - Silva, Daniel Stephanye Filgueiras da; Prata, Nadja Paulino Pessoa; Silva, Izabel Larissa Lucena (Caracol, 2020)
Evidentiality is a category that refers to the source of information. Therefore, we seek to verify the inter-relation between the manifestation of the linguistic phenomenon evidentiality in Spanish and the discursive construction of journalistic articles in J-blog, from the functionalist perspective, more specifically from the Discursive Functional Grammar (DFG). Considering the analysis of articles of j-blogs taken from the two most-read-in Spain- newspapers, we observed that the most used type of source is the defined third, followed by the speaking type (writer). It implies that, although the writer has more ‘freedom’ in its discursive construction, he seems to prefer to identify the other as the origin of the information he conveys, in order to give more ‘credibility’ to his arguments, since he creates the idea that more people share his opinion.